2004
DOI: 10.1359/jbmr.040304
|View full text |Cite
|
Sign up to set email alerts
|

Association of Five Quantitative Ultrasound Devices and Bone Densitometry With Osteoporotic Vertebral Fractures in a Population-Based Sample: The OPUS Study

Abstract: In conclusion, all five QUS devices tested showed significant age-adjusted differences between subjects with and without vertebral fracture. When selecting the strongest variable, QUS of the calcaneus worked as well as central DXA for identification of women at high risk for prevalent osteoporotic vertebral fractures. QUS-based case-finding strategies would allow halving the number of radiographs in high-risk populations, and this strategy works increasingly well for women with more severe vertebral fractures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 250 publications
(141 citation statements)
references
References 50 publications
4
129
0
8
Order By: Relevance
“…QUS is an established osteodensitometric technique in the diagnosis of postmenopausal osteoporosis and a good predictor of fracture risk. 8,19 This radiation-free technique not only provides information on bone mineral content but also on the micro-architecture of bone, like porosity, trabecular orientation, linkage and elasticity, which are all crucial for the mechanical strength of bone. 5,7 In our study, measurements on 114 term and preterm infants within their first week of life, representing bone mineralization as close as possible to the intrauterine situation and least altered by postnatal influence of nutrition or illness, showed a highly significant correlation of QUS with gestational age and birth weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QUS is an established osteodensitometric technique in the diagnosis of postmenopausal osteoporosis and a good predictor of fracture risk. 8,19 This radiation-free technique not only provides information on bone mineral content but also on the micro-architecture of bone, like porosity, trabecular orientation, linkage and elasticity, which are all crucial for the mechanical strength of bone. 5,7 In our study, measurements on 114 term and preterm infants within their first week of life, representing bone mineralization as close as possible to the intrauterine situation and least altered by postnatal influence of nutrition or illness, showed a highly significant correlation of QUS with gestational age and birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…7 Both retrospective and prospective clinical studies have shown that QUS has similar abilities of predicting fracture at the proximal femur and spine in adults as DXA. 8 Although QUS is now widely used in adults and represents a relatively established method for evaluating bone mineral status in the context of diagnosing osteoporosis, QUS has only been employed in mostly small study samples of newborn infants and children. [9][10][11][12][13][14][15][16][17] However, none of these studies provide longitudinal data in regular intervals on QUS measurements in preterm infants simultaneously accounting for growth changes and increase of soft tissue.…”
Section: Introductionmentioning
confidence: 99%
“…OPUS is a prospective population-based study from five European centres and detailed information relating to the population demography and participant recruitment has been published previously (19). The study was approved at each institution according to the Declaration of Helsinki and written consent was obtained from all participants.…”
Section: Osteoporosis and Ultrasound Studymentioning
confidence: 99%
“…The QUS parameters, BUA (broadband sound attenuation) and SOS (speed of sound) depend not only on mineral bone mass, but also on micro architecture and physical properties of bone tissue. A number of studies showed that the values of parameters measured with QUS are lower in woman with the history of osteoporotic fractures, regardless of the bone mineral density determined by DXA (Hernandez, 2004, Gluer, 2004. Thus, QUS parameters are independent risk indicator for hip fractures.…”
Section: Quantitative Ultrasound Of the Heelmentioning
confidence: 99%